Nondestructive Label-Free Mapping of DNA Bioassay Using a Near-Field Scanning Microwave Microscope - Babajanyan, A.; B. Friedman; K. Lee
Near-field scanning microwave microscope (NSMM) is used to readout and visualize homemade 10mer oligonucleotides microarrays of DNA. NSMM instrumentation does not require labeling of target sequences with fluorophores or other tagging groups. Sensitive examination of DNA coverage and high resolution mapping of DNA spots in the microarray were observed by measuring thechange of microwave reflection coefficient (S11) at about 4 GHz operating frequency. The linear dynamicrange for the 10mer nucleotide is over at least 3 orders of magnitude from 0.001pM to 1pM with the detection limit estimated to be approximately 1fM, i.e. 21010 stands/m2.
Keywords: Physics; Electronics; radiowave and microwave technology; direct energy conversion and storage; Cross-Disciplinary